2024
DOI: 10.1111/1365-2656.14120
|View full text |Cite
|
Sign up to set email alerts
|

Predicting organismal response to marine heatwaves using dynamic thermal tolerance landscape models

Andrew R. Villeneuve,
Easton R. White

Abstract: Marine heatwaves (MHWs) can cause thermal stress in marine organisms, experienced as extreme ‘pulses’ against the gradual trend of anthropogenic warming. When thermal stress exceeds organismal capacity to maintain homeostasis, organism survival becomes time‐limited and can result in mass mortality events. Current methods of detecting and categorizing MHWs rely on statistical analysis of historic climatology and do not consider biological effects as a basis of MHW severity. The re‐emergence of ectotherm therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
0
0
0
Order By: Relevance
“…Rezende et al (2014) highlighted that marine species' CTmax could decrease by around 10 and 5°C after 12 h of experiments with bivalves and fishes, respectively. Similarly, Villeneuve and White (2024) showed that CTmax could decrease by 14°C over 15 days compared with 1 min experiments based on three hypothetical species. Given that MHWs last from days to years, the CTmax values obtained from experiments may be overestimated.…”
Section: The Thermal Stress-based Mortality Algorithmmentioning
confidence: 88%
“…Rezende et al (2014) highlighted that marine species' CTmax could decrease by around 10 and 5°C after 12 h of experiments with bivalves and fishes, respectively. Similarly, Villeneuve and White (2024) showed that CTmax could decrease by 14°C over 15 days compared with 1 min experiments based on three hypothetical species. Given that MHWs last from days to years, the CTmax values obtained from experiments may be overestimated.…”
Section: The Thermal Stress-based Mortality Algorithmmentioning
confidence: 88%